Representación social del medio ambiente y de la contaminación del aire : efecto de imbricación de dos objetos (2013)
ABSTRACT: Social representations are forms of social thought, socially built and therefore with a practical use. In the environmental field, this theory has shown a greater interest in understanding the sociocognitive basis underlying to different behaviors and positions of that object of social interest. This study starts from the hypothesis that different environmental objects (water, air, environmental risks, sustainable development), work as a network of representations for being overlapped or anchored in the environment social representation as a policy framework. 305 people participated in the study, half of an urban population exposed to high levels of of the air pollution (Medellin center = exposed) and the other half living in an area with negative indices of the air pollution (Municipality Girardota= unexposed). Through various analyzes that identify the internal organization of environment and air pollution social representations, we try to empirically show the central role of the "risk" factor in the first one. An effect of exposure to air pollution sources is evidence for the second object (air pollution), specifically in the attribution of causes of pollution.